Impact of lower limb stabilization exercises on ankle balance proficiency in collegiate elite athletes with ankle instability - An, Jong-Min; An, Chang-Sik; Yu, Won-Jong; Lee, Chang-Ryeol; Kim, Jeong-Lae (Edelweiss Applied Science and Technology, 2025)
This study aimed to investigate the effects of lower extremity stabilization exercises, including intrinsic foot muscle, gluteus medius, and combined exercises, on balance performance and ankle instability in elite male athletes with chronic ankle instability. This study included 42 elite male athletes from K University in Seoul. The participants were randomly assigned to the intrinsic foot muscle (n = 14), gluteus medius (n = 14), and combination (n = 14) exercise groups. All groups underwent a six-week intervention program, which was conducted three times per week. Each group underwent a common exercise program in addition to their respective interventions. The assessments included the Cumberland Ankle Instability Tool to assess changes in ankle instability scores and tests to measure static and dynamic balance performance. The results revealed improvements in ankle instability scores across all three groups, with no statistically significant differences between them. Significant improvements in static balance were found in the gluteus medius and combination exercise groups. Additionally, all groups demonstrated significant dynamic balance improvements. Notably, the combination exercise group demonstrated greater changes in both static and dynamic balance compared with the other groups. In conclusion, the combination exercise program, which integrates intrinsic foot muscle and gluteus medius exercises, was more effective in improving ankle instability scores and balance performance than the single-component exercise program. Therefore, combining intrinsic foot muscle exercises with gluteus medius exercises effectively improved ankle stability and overall balance. This approach applies not only to elite athletes but also to the general population as a practical and effective intervention method in clinical settings.